2023
DOI: 10.7717/peerj.15395
|View full text |Cite
|
Sign up to set email alerts
|

Triptoquinone A and B exercise a therapeutic effect in systemic lupus erythematosus by regulating NLRC3

Abstract: The autoimmune disorder systemic lupus erythematosus (SLE) is multifaceted, with limited therapeutic alternatives and detrimental side effects, particularly on bones and joints. This research endeavors to examine the curative potential and underlying mechanisms of in addressing SLE-associated bone and joint complications. Triptoquinone A and triptoquinone B, constituents of Tripterygium wilfordii polyglycoside tablets (TGTs), exhibit antioxidant and anti-inflammatory attributes; nonetheless, its function in SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Due to the complexity of the aforementioned compounds, it is evident that a wide range of targets and signaling pathways have been involved in the pharmacological mechanisms of TGT. For example, NLRC3 may be a potential target for TGT treatment of bone and joint complications related to SLE (Xu et al, 2023). Upon investigation of its immunosuppressive effects on adjuvant-induced arthritis (AIA) rats and collagen-induced arthritis (CIA) mice, researchers have found that down-regulating T helper 17 cells (Th17) and upregulating T regulatory cells (Treg) may be the potential mechanism of action (Wang et al, 2008;Astry et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity of the aforementioned compounds, it is evident that a wide range of targets and signaling pathways have been involved in the pharmacological mechanisms of TGT. For example, NLRC3 may be a potential target for TGT treatment of bone and joint complications related to SLE (Xu et al, 2023). Upon investigation of its immunosuppressive effects on adjuvant-induced arthritis (AIA) rats and collagen-induced arthritis (CIA) mice, researchers have found that down-regulating T helper 17 cells (Th17) and upregulating T regulatory cells (Treg) may be the potential mechanism of action (Wang et al, 2008;Astry et al, 2015).…”
Section: Introductionmentioning
confidence: 99%